72.7k views
3 votes
Complete the square x2 – 6x + 8.

Question 3 options:

(x+3)2 – 1


(x-3)2 – 1


(x-3)2


(x-6)2 - 28

2 Answers

4 votes

Answer:

(x - 3)^2 - 1.

Explanation:

x2 – 6x + 8.

We divide the coefficient of x by 2:

-6 / 2 = -3 so the contents of the parentheses is x - 3:

x^2 - 6x + 8

= (x - 3)^2 - (-3)^2 + 8

= (x - 3)^2 - 1.

User Andrew Merrill
by
5.1k points
3 votes


x^2-6x + 8=x^2-6x+9-1=(x-3)^2-1

User Transcendent
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.